Physiotherapy or self-selected exercise in multiple sclerosis: a comparative evaluation of community-based interventions - Davis, Cindy (2008)
Multiple Sclerosis is a major cause of neurological disability in the population of the UK with an incidence of 2,500 new cases diagnosed each year. The estimated number of people affected with MS in the UK is currently believed to be 85,000. (MS Trust 2006). The disease affects those in the prime of their lives as well as those more advanced in years. The reality of living with a progressive neurological condition requires self-management strategies as well as professional involvement. One method of encouraging self-management is the use of exercise to ameliorate some of the problems presented by MS and thus to encourage independence.